2023
DOI: 10.1002/qua.27088
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated motion of cold excitons in conjugated polymers

Abstract: Thermally activated migration of localized cold excitons were investigated in archetypal conjugated polymers; trans‐polyacetylene, polythiophene, and poly(p‐phenylene vinylene). Room temperature thermal energy has been found to provide sufficient energy to avail substantial mobility for excitons. A simple undistorted but displaced harmonic oscillator model has been assumed to predict the activation energy for exciton hopping between identical sites in perfectly planar conjugated chains, promoted by vibrational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…After formation of hot excitons upon photoexcitation, excitons can relax and form relaxed singlet excitons, and at some special circumstances, conversion of singlet excitons into triplet excitons are possible. The relaxation of hot excitons is usually accompanied by the structural rearrangement of the conjugated backbone. , It is generally observed that double bonds in the ground state adopt more single bond character and single bonds adopt more double bond character during relaxation of either singlet or triplet excitons. One salient outcome of this is the planarization of the conjugated backbone due to more double bond character of single bonds connecting ring structures.…”
Section: Resultsmentioning
confidence: 99%
“…After formation of hot excitons upon photoexcitation, excitons can relax and form relaxed singlet excitons, and at some special circumstances, conversion of singlet excitons into triplet excitons are possible. The relaxation of hot excitons is usually accompanied by the structural rearrangement of the conjugated backbone. , It is generally observed that double bonds in the ground state adopt more single bond character and single bonds adopt more double bond character during relaxation of either singlet or triplet excitons. One salient outcome of this is the planarization of the conjugated backbone due to more double bond character of single bonds connecting ring structures.…”
Section: Resultsmentioning
confidence: 99%